Identification of cell cycle-targeting microRNAs through genome-wide screens. Issue 23 (2nd December 2017) - Hydbring, Per; Wang, Yinan; Bogorad, Roman L.; Yin, Hao; Anderson, Daniel G.; Li, Cheng; Sicinski, Piotr
ABSTRACT: By performing nine genome-wide microRNA (miRNA) screens, we recently uncovered a new class of miRNAs, which target multiple cyclins and cyclin-dependent kinases (CDKs). Systemic delivery of selected cell cycle-targeting miRNAs to mouse xenograft models resulted in potent anti-tumorigenic effects without affecting animals' health. Here, we provide an in-depth description of our miRNA screening methodology, analyses of selected cell cycle-targeting miRNAs, and discuss why miRNA therapy might be a viable therapeutic option for cancer patients.